Breast Cancer and Surgery - Bulut, Nilufer (IntechOpen, 2018)
The book 'Breast Cancer and Surgery' summarizes the treatment options from the onset of breast carcinogenesis to early-local advanced and metastatic breast cancer. Chemotherapy alternatives, drug resistance and local and surgical treatment preferences are extensively discussed and this information is especially directed at clinicians, researchers, and students. This book includes a comparison between different chemotherapy agents and targeted therapies with published phase II-III studies. The importance of palliative care and dietary supplements administered during the treatment course in reducing the comorbidity of patients is emphasized. Photodynamic treatments have been included in this book. A comprehensive and up-to-date information exchange that can be accessed through a single source is provided to all researchers interested in breast cancer.